The Evolution of Juventae Chasma, Valles Marineris, Mars: Progressive Collapse and Sedimentation. Issue 11 (9th November 2017) - Fueten, F.; Novakovic, N.; Stesky, R.; Flahaut, J.; Hauber, E.; Rossi, A. P.
Abstract: Juventae Chasma is an isolated chasm located north of the interconnected chasms within Valles Marineris. It contains four separate interior layered deposit (ILD) mounds. We have combined layer measurements, as well as mineralogical data of the mounds with topographic data of the remaining chasm and the surrounding plateau. Our observations indicate that the chasm underwent a complex geological history. We suggest that individual ILD mounds are not contemporaneous with each other and a series of progressive collapses enlarged an initially smaller chasm to its current shape. ILDs were deposited in a lacustrine setting, and the time of ILD deposition was limited. Basin collapse and chasm enlargement continued beyond the time of ILD deposition and thus were not driven by sediment load. Glacial processes appear to have played a role in the late, postlacustrine history of the chasm. We present a simplified model that highlights some of the complexity of the chasm evolution, but acknowledge that the true history is undoubtedly more complicated. Key Points: Interior layered deposit formed in lacustrine setting, but they did not all form at the same time Basin collapse did not occur as a single event and was not driven by sediment load Geological history of chasma evolution is complex